Combined mechanical mitral valve replacement and transmitral myectomy for hypertrophic obstructive cardiomyopathy treatment: An experience of over 20 years. Issue 4 (April 2019) - Shimahara, Yusuke; Fujita, Tomoyuki; Kobayashi, Junjiro; Fukushima, Satsuki; Kume, Yuta; Yamashita, Kizuku; Matsumoto, Yorihiko; Kawamoto, Naonori; Tadokoro, Naoki; Kakuta, Takashi; Kanzaki, Hideaki; Amaki, Makoto
Highlights: Left ventricular intracavitary gradient decreased postoperatively (16.8 mmHg vs. 107.4 mmHg). Freedom from cardiac death was 92.8%, 89.0%, and 80.1% at 5, 10, and 15 years. Freedom from heart-failure hospitalization was 87.7% and 82.2% at 5 and 10 years. Mitral valve replacement remains a viable option in certain situations. Optimal postoperative medical treatment and close clinical follow-up are necessary. Abstract: Background: Although transaortic septal myectomy (TASM) is recognized as a standard procedure for treating hypertrophic obstructive cardiomyopathy (HOCM), occasionally the left ventricle (LV) intracavitary gradient remains postoperatively because of this technically demanding procedure. Mitral valve replacement (MVR) is sometimes chosen as an alternative option, but data on its long-term outcomes are lacking. Methods and results: Between 1991 and 2016, 29 patients [age, 14–82 (mean 58.9 ± 15.9) years; 22 female patients (75.9%)] underwent combined mechanical MVR and transmitral myectomy. Of these, six patients had undergone MVR following a second cardiac arrest because of the residual LV outflow gradient or residual mitral regurgitation following TASM. Concomitant TASM was performed in 13 patients. The LV intracavitary gradient at rest assessed by transthoracic echocardiography significantly decreased postoperatively (16.8 ± 19.1 mmHg vs. 107.4 ± 52.5 mmHg, p < 0.0001). Actuarial freedom rates from cardiac death were 92.8%, 89.0%, and 80.1% at 5, 10, and 15 years postoperatively, respectively. Sudden death occurred in three of the four patients who died of late cardiac complications. None of these patients with sudden death had implantable cardioverter-defibrillators. Most patients had maintained their LV end-diastolic dimension at <50 mm for 10–15 years postoperatively. Actuarial freedom rates from hospitalization for heart failure were 87.7%, 82.2%, and 54.8% at 5, 10, and 15 years postoperatively, respectively. Occurrence rates of cerebral hemorrhage and infarction were 0.6% per patient-year and 1.3% per patient-year, respectively. Conclusions: Combined mechanical MVR and myectomy is an effective procedure to eliminate the LV intracavitary gradient in patients with HOCM. Although this procedure remains a viable option in certain situations, optimal medical treatment and close clinical follow-up along with the cooperation between cardiac surgeons and cardiologists are necessary to achieve favorable long-term outcomes.